Efforts to Address the Rising Cases of Divorce: Mahmud Syaltut’s Perspective - Husnawadi (Journal of Islamic Religious Studies, 2025)
This study is motivated by the limited research on preventive measures against divorce, despite its significant impact on family stability and social harmony in Muslim communities. The study aims to describe and analyze Mahmud Syaltut’s perspective on overcoming the increasing number of divorce cases. The research adopts a qualitative descriptive design, using literature as the primary source, with data collected by visiting libraries and examining books and scholarly works relevant to the research theme. Data were analyzed through thematic analysis and presented descriptively to provide a comprehensive understanding of preventive strategies. The findings reveal that tackling the rising divorce rate can be achieved through four main measures: selecting a prospective wife with noble morals and strong religious commitment, proposing marriage according to proper Islamic procedures, ensuring that husband and wife uphold their respective rights and obligations after marriage, and avoiding domination or undue interference by parents or extended family in family matters. These results align with the objectives of the study and support existing Islamic legal scholarship emphasizing ethical marital conduct, moral integrity, and family stability. The study concludes that Mahmud Syaltut’s guidance provides practical and ethically grounded strategies that can serve as a reference for married couples, families, and society. The implications encompass theoretical contributions to Islamic family law literature and practical recommendations for policymakers, religious scholars, and community leaders to promote marital education, counseling, and preventive measures against divorce. Additionally, this study identifies future research opportunities on empirical testing of these preventive strategies in diverse social and cultural contexts.